Use of efficient weeding tools to reduce farmers’ drudgery ingg tolss to reduce farmers’ drudgery - Chetan, C. R.; Sarkar, Bikash; Singh, P. K.; Chander, S.; Ghosh, D.; Choudhary, V. K.; Reddy, R. B. (Indian Farming, 2018)
Manual weeding operations are drudgeries and laborious one, whichaccounts 25% of the total labour requirement during a cultivationseason. Energy requirement of khurpi is the least but the work output is also the lowest, where as the wheel hoes (push - pull type) and the selfpropelled power weeders covers a maximum area with acceptable physiological demand, work performance and workers preference. Hence, use of improved weeding tools viz., grubber, wheel hoes, and power weeders etc. is essential to reduce human drudgery and to enhance operator’s comfortness in weed management.